1999
DOI: 10.1021/jp990691p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Collision Energy on the O(1D) + RH → OH(X2Π) + R (RH = CH4, C2H6, C3H8) Reaction Dynamics:  A Laser-Induced Fluorescence and Quasiclassical Trajectory Study

Abstract: The influence of the collision energy (E T) on the O(1D) + RH → OH(X2Π) + R (RH = CH4, C2H6, and C3H8) reaction dynamics has been studied, using the N2O photodissociation at 193 nm as O(1D) precursor (〈E T〉 = 0.403 eV) and probing the OH v‘ ‘ = 0 and 1 levels by LIF. A triatomic QCT study of the reaction with CH4 on a fully ab initio based analytical PES has also been performed, and a quite good agreement with the experimental OH rovibrational distributions has been obtained. Our experimental results are simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
49
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 35 publications
12
49
0
Order By: Relevance
“…Moreover, we have also considered a spin-orbit correction as in recent similar studies, 33,35 to take into account the two NO reactant spin-orbit states for reactions ͑1͒ and ͑2͒. Thus, the electronic partition function ͓Q(T)͔ of NO(X 2 ⌸) is given by…”
Section: Variational Transition-state Thermal Rate Constantsmentioning
confidence: 99%
“…Moreover, we have also considered a spin-orbit correction as in recent similar studies, 33,35 to take into account the two NO reactant spin-orbit states for reactions ͑1͒ and ͑2͒. Thus, the electronic partition function ͓Q(T)͔ of NO(X 2 ⌸) is given by…”
Section: Variational Transition-state Thermal Rate Constantsmentioning
confidence: 99%
“…[4][5][6] The CH 3 OH reaction intermediate can be formed rather easily via insertion of O( 1 D) into a C-H bond of methane. 4,6,24,36,37 The particular importance of the CH 3 + OH channel (which has a kinematics nearly identical to reactants) is probably due to the fact that the other channels are less exoergic or present a barrier with respect to CH 3 OH.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The effect of the O( 1 D) + CH 4 collision energy (relative translational energy of reactants, E c ) on the OH product vibrational state distributions, has been measured by infrared (IR) emission and related techniques 20, 25 and by laser-induced fluorescence (LIF). 19,[21][22][23][24] The rotational state distributions were also determined experimentally in Refs. 19 and 22-24.…”
Section: Introductionmentioning
confidence: 99%
“…Similar bimodal distributions to some extent have rather been observed in the exothermic reactions of electronically excited atomic oxygen O( 1 D) with saturated hydrocarbon reactions. [13][14][15][16][17][18] Wiesenfeld et al found that the major high-NЉ regime ͑about 80% of the relative yields͒ was ascribed to the short-lived insertion process and adequately described by the linear surprisal. It was also possible to deduce the population of the low-NЉ regime by subtracting the prior distribution scaled by the surprisal parameter from the nascent distribution.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…In addition, two microscopic reaction pathways for the minor OH channel have been proposed to understand the characteristic bimodal rotational distributions of OH product: the low-and high-NЉ components. [13][14][15][16][17][18][19][20][21][22] While the low-NЉ components are formed from the long-lived alcohol intermediate produced by the insertion reaction of O( 1 D) into a C-H bond, the high-NЉ components are characterized by the process undergoing a short-lived insertion complex.…”
Section: Introductionmentioning
confidence: 99%